Evaluation of a Centralized Response to Domestic Violence by the San Diego County Sheriff's Department Domestic Violence Unit, 1998-1999 - Pennell, Susan ([Verlag nicht ermittelbar], 2002)
This study examined the implementation of a specialized domestic violence unit within the San Diego County Sheriff's Department to determine whether the creation of the new unit would lead to increased and improved reporting, and more filings for prosecution. In order to evaluate the implementation of the specialized domestic violence unit, the researchers conducted the following tasks: (1) They surveyed field deputies to assess their level of knowledge about domestic violence laws and adherence to the countywide domestic violence protocol. (2) They studied a sample from the case tracking system that reported cases of domestic violence handled by the domestic violence unit to determine changes in procedures compared to an earlier case tracking study with no specialized unit. (3) They interviewed victims of domestic violence by phone to explore the responsiveness of the field deputies and the unit detectives to the needs of the victims. Part 1 (Deputy Survey Data) contains data on unit detectives' knowledge about the laws concerning domestic violence. Information includes whether or not the person considered the primary aggressor was the person who committed the first act of aggression, if a law enforcement officer could decide whether or not to complete a domestic violence supplemental report, whether an arrest should be made if there was reasonable cause to believe that a misdemeanor offense had been committed, and whether the decision to prosecute a suspect lay within the discretion of the district or city attorney. Demographic variables include deputy's years of education and law enforcement experience. Part 2 (Case Tracking Data) includes demographic variables such as race and sex of the victim and the suspect, and the relationship between the victim and the suspect. Other information was collected on whether the victim and the suspect used alcohol and drugs prior to or during the incident, if the victim was pregnant, if children were present during the incident, highest charge on the incident report, if the reporting call was made at the same place the incident occurred, suspect actions described on the report, if a gun, knife, physical force, or verbal abuse was used in the incident, if the victim or the suspect was injured, and if medical treatment was provided to the victim. Data were also gathered on whether the suspect was arrested or booked, how the investigating officer decided whether to request that the prosecutor file charges, type of evidence collected, if a victim or witness statement was collected, if the victim had a restraining order, prior history of domestic violence, if the victim was provided with information on domestic violence law, hotline, shelter, transportation, and medical treatment, highest arrest charge, number of arrests for any drug charges, weapon charges, domestic violence charges, or other charges, case disposition, number of convictions for the charges, and number of prior arrests and convictions. Part 3 (Victim Survey Data) includes demographic variables such as victim's gender and race. Other variables include how much time the deputy spent at the scene when s/he responded to the call, number of deputies the victim interacted with at the scene, number of deputies at the scene that were male or female, if the victim used any of the information the deputy provided, if the victim used referral information for counseling, legal, shelter, and other services, how helpful the victim found the information, and the victim's rating of the performance of the deputy.